Melatonin use in unilateral total salpingectomy in rats - Sapmaz, E.; Kale, A.; Akpolat, N. (I R O G Canada, Inc, 2012)
Objective: To investigate the effects of melatonin use in unilateral total salpingectomy on ovarian histology in rats. Setting: Firat University, Medical School, Obstetrics and Gynecology Department, Elazig. Material and Method: Thirty adult, female rats of Wistar albino species with regular cycles were randomly allocated to three groups in the estrus phase. G1 (n: 10): The group where the abdomen was opened and closed, and left oophorectomy was performed six months later. G2 (n: 10): The group where left total salpingectomy was performed and followed by left oophorectomy six months later. G3 (n: 10): The group where the abdomen was opened, left total salpingectomy was performed 15 min after 10 mg/kg/IP melatonin administration, and left oophorectomy was performed six months later. Samples of the left ovary were fixed in formaldehyde. The preparations were stained with hematoxylineosin, and primordial, primary, secondary and tertiary follicles were counted. All the numbers were added up to determine the ovarian follicle reserve. Atretic follicles were counted. Corpus luteum and corpus albicans were counted. Number of total corpuses was calculated. Regression of the presence of angiogenesis within the corpus luteum was examined. Presence of fibrosis on the ovarian stroma was examined. An ordinal scale was formed for the presence of regression of angiogenesis within the corpus luteum and presence of fibrosis (none: 0p, present: 1p, markedly present: 2p). Follicle cysts in the ovary were counted. Kruskal Wallis variance analysis was used in the statistical analysis of data; p < 0.05 was considered significant. Results: Primordial follicle count, ovarian follicle reserve and regression of angiogenesis in the corpus luteum were found to be significantly lower (p < 0.05, Mann-Whitney U test), and atretic follicle count, microscopic follicle cyst and fibrosis development were found to be significantly higher in G2, when compared to G1 and G3 (p < 0.05, Mann-Whitney U test). None of the rats in G1 and G3 had ovarian cysts, whereas five rats in G2 were identified as having macroscopic follicle cysts. Other data were found to be similar in G1, G2, and G3 (Kruskal Wallis variance analysis). Conclusion: Left total salpingectomy reduces primordial follicles, ovarian follicle reserve and regression of angiogenesis in the corpus luteum, while increasing atretic follicles, microscopic ovarian cysts and fibrosis development. It leads to the development of macroscopic follicle cysts in the ovary at a high rate (50%) in the sixth month. Melatonin use eliminates these harmful effects. Melatonin can be used to avoid the unfavorable effect of total salpingectomy on the ovary.
Keywords: Melatonin; Ovarian histology; Rat; Total salpingectomy